Фізіологічні механізми адаптації рослин Iris hybrida hort. до несприятливих умов перезимівлі у Лісостепу України - Skrypka, G.І.; Makarova, D.G.; Kytayev, O.I.; Horobets, V.F.; Buidin, Y.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The degree of winter hardiness of Iris hybrida hort. in Forest-Steppe of Ukraine was determined. Physiologic mechanisms that enable hardening of Iris hybrida plants for cold weather conditions were studied.